Utilisation of various bonding modes of nitrogen-rich heterocycles in gold(I) chemistry - Gabrielli, William Fullard (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD (Chemistry and Polymer Science))—University of Stellenbosch, 2006.